Health and its care as an intersubjective cultural relationship: phenomenological reflection in Schütz - Guerrero Castañeda, Raul Fernando (2020)
The objective of this essay was to reflect on health and care as an intersubjective cultural relationship, taking up some of Alfred Schütz's concepts such as intersubjectivity, culture and the world of life. Health comprises an objective meaning and at the same time a subjective one, its care will depend on the conscience of the people and their intention; furthermore it is also determined by a collective conscience. The role of culture as a form of relational communication between human beings and between various knowledge that depend on the ways of life that have been maintained for generations and that continue to have different forms of experiencing health is highlighted. It is concluded that health must be a value in a broadly strict sense, where the social perspective and the recreation of meanings around the experience are considered; In other words, social coexistence grants meanings that are visible in everyday life. It is imperative for nursing and health professionals to integrate culture as a way of approaching health care.